2019
DOI: 10.1007/s00429-019-01981-y
|View full text |Cite
|
Sign up to set email alerts
|

White-matter microstructural properties of the corpus callosum: test–retest and repositioning effects in two parcellation schemes

Abstract: White-matter microstructural properties of the corpus callosum: Test-retest and repositioning effects in two parcellation schemes. Brain Structure and Function, 224(9),[3373][3374][3375][3376][3377][3378][3379][3380][3381][3382][3383][3384][3385]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The CC is a large and compact WM fiber bundle that has homogenous directionality, that is, without curves or crossing fibers, and consequently, has high anisotropy (Anand et al, 2019; Fabri, 2014; Hasan et al, 2005). For this reason, the CC can be considered as a good reference region in repeatability studies, and where achieving high repeatability is expected.…”
Section: Discussionmentioning
confidence: 99%
“…The CC is a large and compact WM fiber bundle that has homogenous directionality, that is, without curves or crossing fibers, and consequently, has high anisotropy (Anand et al, 2019; Fabri, 2014; Hasan et al, 2005). For this reason, the CC can be considered as a good reference region in repeatability studies, and where achieving high repeatability is expected.…”
Section: Discussionmentioning
confidence: 99%
“…The CC was divided into 10 regions of interest (ROIs), following the scheme described by Björnholm et al ( 2017) and modi-fied by Anand et al (2019). The CC regions were demarcated on the midsagittal slice in the Montreal Neurological Institute (MNI152) standard space using the FMRIB Software Library's FSL view (Jenkinson et al 2012).…”
Section: Segmentation Of the CCmentioning
confidence: 99%
“…This is consistent with increased water mobility in an expanded intra-and extracellular space, and presence of largediameter axons with greater interaxon distances. Thus, in addition to its high reliability (Anand et al 2019), geomT 2IEW emerges as a sensitive index of white matter microstructure suitable for the future in vivo examination of its correlates. In addition, the trend of increasing average axon diameter from the genu to the splenium (LaMantia and Rakic 1990a; Aboitiz et al 1992), mirroring the relative trend observed in the MWF, supports the proposition that MWF reflects myelin content driven potentially by the average diameter of fibers in white matter tissue.…”
Section: Regional Differences In Callosal Microstructurementioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the CC parcellation into callosal regions allows for a precise differentiation of motor connectivity and the structural integrity of these tracts in the CC [10]. Thus, the CC parcellation should be so helpful to better understand inter-hemispherical callosal connectivity in patients or healthy subjects [11]. In particular, MRI takes advantage of the macroscopic geometrical arrangement of white matter bundles that it makes capable of generating good CC visualization from the sagittal plane.…”
Section: Introductionmentioning
confidence: 99%